Comparison of antianginal and antiischemic efficacy of cytoprotectors, nitrates, and beta-blockers during monotherapy and combined therapy in patients with effort angina and silent myocardial ischemia episodes - S. N. Vaslyaeva; O. V. Zygankova; I. G. Gordeev; N. A. Volov (Российский кардиологический журнал, 2004)
In 57 patients with stable effort angina, functional class II-III, and episodes of silent myocardial ischemia, antianginal and antiischemic efficacy of trimetazidine, isosorbide-5-mononitrate, and nadolol (monotherapy and combined therapy) was compared. According to the results obtained, trimetazidine had sufficiently high efficacy and safety. Nevertheless, antiischemic efficacy of nadolol was higher than that for isosorbide-5-mononitrate and trimetazidine. Combination of trimetazidine and hemodynamically active preparations did enhance antiischemic action, without adverse circulatory effects. This additive effect was maximal for trimetazidine and nadolol combination.